Statistics of retirement age around the world - Ismail, Fadillah; Nasuredin, Juzaimi; Humaid Alhosani, Adnan Ali Hassan; Maulad Bahrol, Khadijah; Nojumuddin, Nur Syereena (Penerbit Uthm, 2019)
Retirement can possibly be a distressing life progress in late adulthood, frequently setting off a wide scope of huge changes, for example, lost stable salary, detachment from partners at work and an expansion in unstructured time. Most people spend their adult years in the workhour so retirement represents freedom and rest. Retirement ages, or the age when some sort of government pension can be received, differs around the world. The Organisation for Economic Co-operation and Development (OECD) average for a normal pension age is currently 64.3 years for men and 63.7 years for women (Baker, 2018).